1996
DOI: 10.1128/aac.40.8.1775
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of differential activities of ofloxacin enantiomers

Abstract: Ofloxacin, a potent quinolone antibacterial agent, has a tricyclic ring structure with a methyl group attached to the asymmetric carbon at the C-3 position on the oxazine ring. The S isomer (DR-3355) of ofloxacin has antibacterial activity up to 2 orders of magnitude greater than that of the R isomer (DR-3354). This differential antibacterial activity was not due to different drug transport mechanisms of the two isomers but was found to be derived from the inhibitory activity against the target enzyme, DNA gyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 33 publications
1
59
0
1
Order By: Relevance
“…Both enantiomers have been found to bind to calf thymus DNA with higher affinity for the S-isomer than the R-isomer [5,6]. It is well-known that metal ions coordinate to quinolones, and several complexes have been isolated and characterized [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…Both enantiomers have been found to bind to calf thymus DNA with higher affinity for the S-isomer than the R-isomer [5,6]. It is well-known that metal ions coordinate to quinolones, and several complexes have been isolated and characterized [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…Ofloxacin is a potent quinolone antibacterial agent marketed as enantiomerically pure S-(À)-ofloxacin since 1995, although it can be marketed as the racemic mixture too. It has been reported that the S-(À)-enantiomer has antibacterial activity up to 2 orders of magnitude greater than that of the R-(þ)-enantiomer due to the greater binding potency of the S(À)-enantiomer to the enzyme-DNA complex [35]. S-(À)-ofloxacin is excreted from the body unchanged and up to date no chiral inversion has been reported in the environment.…”
Section: Application To Environmental Samplesmentioning
confidence: 99%
“…Further consecutive reactions enable the amplification of ee to produce the highly enantiomerically enriched alkanol 22 with the absolute configurations corresponding to that of the D-or L-Cr(acac) 3 . The chiral hydrocarbons, 1,1 0 -binaphthyl [81], [6]-and [5]-helicenes [82] and allene [83] can act as chiral initiators of asymmetric autocatalysis.…”
Section: Asymmetric Autocatalysis With Amplification Of Ee Initiated mentioning
confidence: 99%
“…The previous commercial drug was a racemic mixture, which included almost the same amount of S-and R-enantiomers. However, it was discovered that the S-enantiomer is more active than the R-enantiomer [5]. Thus, the present drug has been constituted only from the S-enantiomer.…”
Section: Introductionmentioning
confidence: 97%